Suhakam's Recommendations and Its Application In The Peaceful Assembly Act 2012 - Mazita Mohamed; Haslinda Mohd Anuar; Azlin Namili Mohd Ali; Muhammad Firdaus Bidin; Rohana Abdul Rahman; Rusniah Ahmad (UUM Journal of Legal Studies, 2016)
In Malaysia, a provision on peaceful assembly is stipulated under Article 10 of the Federal Constitution which combines the freedom of speech, peaceful assembly and association. However, these freedoms have restrictions which are usually justified under the broad stroke of maintaining racial harmony and public order. Prior to 23 April 2012, section 27 of the Police Act was implemented to govern a public assembly, and the enactment of the Peaceful Assembly Act 2012 (PAA 2012), then, gives some light to the right of assemble peacefully. The objective of this article is to examine by comparing SUHAKAM’s recommendations with the Peaceful Assembly Act 2012. To achieve the objective, the doctrinal legal research has been used, specifically the analytical and comparative methods.